Epidermal growth factor receptor inhibition by anti‐CD147 therapy in cutaneous squamous cell carcinoma. Issue 2 (16th June 2015) - Frederick, John W.; Sweeny, Larissa; Hartman, Yolanda; Zhou, Tong; Rosenthal, Eben L.
Abstract: Background: Advanced cutaneous squamous cell carcinoma (SCC) is an uncommon and aggressive malignancy. As a result, there is limited understanding of its biology and pathogenesis. CD147 and epidermal growth factor receptor (EGFR) have been identified as oncologically important targets, but their relationship remains undefined in cutaneous SCC. Methods: Multiple cutaneous SCC cell lines (Colo‐16, SRB‐1, and SRB‐12), were treated in vitro with a range of chimeric anti‐CD147 monoclonal antibody (mAb) (0, 50, 100, and 200 µg/mL) or transfected with a small interfering RNA against CD147 (SiCD147). Cell proliferation, migration (scratch wound healing assay), and protein expression was then assessed. In vivo, Colo‐16 flank xenografts were treated anti‐CD147 mAb (150 µg i.p. triweekly). Results: After treatment with anti‐CD147 (200 µg/mL), there was a significant decrease in proliferation for all cell lines relative to controls ( p < .005). In addition, treatment with anti‐CD147 (200 µg/mL) resulted in decreased cell migration for all cell lines, with an average of 43% reduction in closure compared to controls ( p < .001). Colo‐16 SiCD147 expression demonstrated similar reduction in proliferation and wound closure. Anti‐CD147 antibody therapy and siRNA mediated reduction in CD147 expression were both found to decrease protein expression of EGFR, which correlated with a reduction in downstream total and phosphorylated protein kinase B (pAKT). Tumor growth in vivo was reduced for both the anti‐CD147 treatment group and the SiCD147 group relative to controls. Conclusion: Inhibition and downregulation of CD147 in cutaneous SCC resulted in suppression of the malignant phenotype in vitro and in vivo, which may be mediated in part by an alteration in EGFR expression. As a result, CD147 may serve as a potential therapeutic target for advanced cutaneous SCC. © 2014 Wiley Periodicals, Inc. Head Neck 38: 247–252, 2016